Kekuatan Akta Pejabat Pembuat Akta Tanah dalam Proses Jual Beli Tanah Kavling - Made Agus Satria Wahyudi; Ida Ayu Putu Widiati; Luh Putu Suryani (Warmadewa Press, 2021)
Indonesian people, especially Balinese, often do business on land in various ways, including buying and selling land. The first formal certificate of ownership should clearly define rights and obligations, provide legal certainty, and be useful in the event of a dispute over the purchased land. The purposes of this study are to explain the process of buying and selling land in plots of land and the strength of the deed of the official who made the land deed. The method applied in this research is the Law-Based Survey with a statutory approach and a conceptual approach. Data collection techniques were carried out by field observations in the form of interviews. Sources of legal materials used are primary and secondary sources of legal materials. The data analysis technique used descriptive qualitative analysis method. The results show that if an authentic deed made by PPAT does not meet the requirements as an authentic deed, then the authentic deed is accredited as a private deed. If there is a problem and the certificate for certain plots of land has not been issued, the Land Office will wait until there is a final and binding decision from the Court regarding the status of the land in question and will continue to delay the process of land certification for the plots concerned. If you want to buy land, of course you have to investigate material requirements, property status, letters or other important documents, of course there should be no dispute.